HUBUNGAN KECERDASAN SPIRITUAL DENGAN RESILIENSI PADA SISWA YANG MENGIKUTI PROGRAM AKSELERASI - Theresia Oktaviani Nay; Dewanti Ruparin Diah (University of Merdeka Malang, 2013)
The study was conducted to determine the relationship between spiritual intelligence with resilience in students who attend an accelerated program. The populations in this study were students at SMAN acceleration in Malang as many as 194 students. The samples in this study were female students of SMAN accelerated program in the city of Malang by 55 students. Sampling in this study use purposive sampling technique. The process of data analysis is the product moment correlation. Results for resilience scale of 60 items made as many as 54 valid item items. As for the scale of spiritual intelligence of 60 items made, as much as 55 valid item items. Reliability test results obtained values for resilience scale reliability coefficient of 0.917. As for the spiritual intelligence scale values obtained reliability coefficient of 0.935 so that the reliability test results showed the existence of a reliable degree. The results of the analysis of data obtained r count greater than r table (0.687 0.266) with a correlation index (r xy) of 0.687 at a significance level of 0.05 which indicates that there is a positive relationship between the resilience of the spiritual intelligence, so that the working hypothesis (Ha) states that there is a relationship between resilience with spiritual intelligence, accepted.